Electrochemical degradation of the antibiotic ciprofloxacin in a flow reactor using distinct BDD anodes: Reaction kinetics, identification and toxicity of the degradation products. (November 2019) - Wachter, Naihara; Aquino, José Mario; Denadai, Marina; Barreiro, Juliana C.; Silva, Adilson José; Cass, Quezia B.; Bocchi, Nerilso; Rocha-Filho, Romeu C.
Abstract: The performances of distinct BDD anodes (boron doping of 100, 500 and 2500 ppm, with sp 3 /sp 2 carbon ratios of 215, 325, and 284, respectively) in the electrochemical degradation of ciprofloxacin – CIP (0.5 L of 50 mg L −1 in 0.10 M Na2 SO4, at 25 °C) were comparatively assessed using a recirculating flow system with a filter-press reactor. Performance was assessed by monitoring the CIP and total organic carbon (TOC) concentrations, oxidation intermediates, and antimicrobial activity against Escherichia coli as a function of electrolysis time. CIP removal was strongly affected by the solution pH (kept fixed), flow conditions, and current density; similar trends were obtained independently of the BDD anode used, but the BDD100 anode yielded the best results. Enhanced mass transport was achieved at a low flow rate by promoting the solution turbulence within the reactor. The fastest complete CIP removal (within 20 min) was attained at j = 30 mA cm −2, pH = 10.0, and q V = 2.5 L min −1 + bypass turbulence promotion. TOC removal was practically accomplished only after 10 h of electrolysis, with quite similar performances by the distinct BDD anodes. Five initial oxidation intermediates were identified (263 ≤ m/z ≤ 348), whereas only two terminal oxidation intermediates were detected (oxamic and formic acids). The antimicrobial activity of the electrolyzed CIP solution was almost completely removed within 10 h of electrolysis. The characteristics of the BDD anodes only had a marked effect on the CIP removal rate (best performance by the least-doped anode), contrasting with other data in the literature. Highlights: The BDD100 anode yielded the fastest removal of ciprofloxacin (CIP). Similar TOC removal rates were attained with the three distinct BDD anodes. Mass transport was enhanced by promoting the solution turbulence within the reactor. Most of the antimicrobial activity was removed within 10 h of electrolysis.